Frictional Behaviour of Thin Tin Films with a Copper Interlayer - Komlossy, Martin; Dzimko, Marian; Takeichi, Yoshinori; Uemura, Masao (Communications - Scientific letters of the University of Zilina, 2005)
Generally, the purpose of the study is to know the effect of temperature during tin-films deposition on frictional behaviour and lifetime of a tin layer with copper interlayer. In a recent study an experimental approach was performed to investigate the effect of a copper interlayer thickness on frictional behaviour of thin films. In this experiment, copper of 2 m thickness was deposited between the steel substrate and tin films of 1 m and 2 m thicknesses in vacuum environment without and with the heating of the substrate up to 300 °C. The friction tests were performed to determine the friction coefficient and lifetime of lubrication capability.